Impurity effects on binding energy, diamagnetic susceptibility and photoionization cross-section of chalcopyrite AgInSe2 nanotadpole. (15th June 2022) - Mantashian, Grigor A; Hayrapetyan, David B
Abstract: Recently the interest in chalcopyrite semiconductor nanostructures has increased because of their non-toxicity and their wide direct bandgap. Likewise, structures with non-trivial geometry are particularly interesting because of their electronic, optical, and magnetic properties. In the current article, the finite element method was used in conjunction with the effective mass approximation to theoretically investigate the properties of a chalcopyrite AgInSe2 nanotadpole in the presence of an hydrogen like shallow off-center impurity. The morphology of the nanotadpole gives it excellent hydrodynamic properties and is ideal for a wide range of applications. The probability densities for various impurity positions and energy levels were obtained. The results suggested a strong dependence of the behavior of the electron on the impurity positions and the orientation of the wave function. The investigation of the nanotadpole's energy spectra and their comparison with the cylindrical and spherical quantum dots suggest that the spectrum has degenerate states similar to the spherical case, however at some ranges, the levels behave similarly to the cylindrical case. The binding energy's dependence on the nanotadpole's size and the impurity position was obtained. The dependence of the diamagnetic susceptibility on the impurity position was calculated. An extensive investigation of the photoionization cross-section was carried out for the ground and the first two excited states as the initial states and the first twenty excited states as the final states.